2020
DOI: 10.4014/jmb.2005.05007
|View full text |Cite
|
Sign up to set email alerts
|

Reduction of Trimethylamine Off-Odor by Lactic Acid Bacteria Isolated from Korean Traditional Fermented Food and Their In Situ Application

Abstract: Trimethylamine (TMA) is an organic and volatile fatty amine known to cause acute health problems such as pulmonary stimulation, eye irritation, and liver failure [1]. The source of TMA is a nitrogenous organic compound named trimethylamine N-oxide (TMAO). TMAO is an oxidized form of TMA isolated from seawater and known to present in large quantities in fish muscle and tissue [2][3][4]. Most marine fish and shellfish have mechanisms for digesting TMAO, usually by the osmoregulation process. Similarly, in frozen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(6 citation statements)
references
References 20 publications
0
6
0
Order By: Relevance
“…Ligilactobacillus , a probiotic producing lactic acid in the gut, is associated with various health benefits and diarrhea alleviation. Studies have shown that bacterial-produced lactic acid can significantly reduce TMA levels ( An et al, 2011 ; Park et al, 2020 ; Guerrero Sanchez et al, 2022 ), and CutC activity directly influences the production of TMA, a precursor to TMAO. It can be inferred that Ligilactobacillus may inhibit CutC activity and reduce TMA production by generating lactic acid.…”
Section: Discussionmentioning
confidence: 99%
“…Ligilactobacillus , a probiotic producing lactic acid in the gut, is associated with various health benefits and diarrhea alleviation. Studies have shown that bacterial-produced lactic acid can significantly reduce TMA levels ( An et al, 2011 ; Park et al, 2020 ; Guerrero Sanchez et al, 2022 ), and CutC activity directly influences the production of TMA, a precursor to TMAO. It can be inferred that Ligilactobacillus may inhibit CutC activity and reduce TMA production by generating lactic acid.…”
Section: Discussionmentioning
confidence: 99%
“…The treatment developed in the case of TMA removal seems to be of higher performance than reported in the literature. Indeed, Park et al (2020) [10] observed that lactic acid bacteria were able to remove up to 62% of the TMA content of spoiled fish, while Jo et al ( 2021) [11] instead identified the use of such microorganisms as a strategy to prevent the formation of TMA in ribbonfish fillets. Similarly, the use of tea polyphenols in clam hydrolysate was identified as a strategy to prevent the formation of TMA [7].…”
Section: General Discussion On Volatile Compoundsmentioning
confidence: 99%
“…To overcome off-flavors in marine resources, several deodorization strategies have already been proposed including fermentation, use of antioxidants, and adsorption processes [7,[10][11][12][13]. Even if these strategies have demonstrated their relevance at different degrees, they all seem to be associated with drawbacks, thus hampering their extensive use.…”
Section: Introductionmentioning
confidence: 99%
“…While Lactobacilli species belongs to the Firmicutes phylum, these bacteria seem to reduce TMAO levels to prevent atherosclerosis and hypertension by unknown exact mechanisms ( Zhao et al, 2021 ). However, as aforementioned, marine studies have established that the lactic acid produced by the bacteria is able to significantly reduce trimethylamine levels ( Park et al, 2020 ), and the bacterial species are not included among those containing the choline trimethylamine-lyase ( CutC ) and its activating enzyme CutD gene responsible for TMAO production ( Kalnins et al, 2015 ; Romano et al, 2015 ; Rath et al, 2017 ). A human study assessing the benefit of Lactobacili was a randomised, double blind, placebo-controlled study which showed that consumption of Lactobacillus helveticus fermented milk product reduced systolic blood pressure by 5.2 mmHg and diastolic blood pressure by 2.0 mmHg in 46 borderline hypertensive men ( Mizushima et al, 2004 ).…”
Section: Potential Therapies In Hypertension By Alteration Of Gut Mic...mentioning
confidence: 99%